Hinokitiol suppressed pan-histone expression and cell growth in oral squamous cell carcinoma cells. (May 2015) - Shih, Yin-Hua; Chang, Kuo-Wei; Yu, Cheng-Chia; Kao, Ming-Ching; Chen, Michael Yuanchien; Wang, Tong-Hong; Chi, Tzu-Yun; Chen, Yi-Ling; Shieh, Tzong-Ming
Highlights: Hinokitiol exhibited more cytotoxicity to OSCC cells than normal oral cells. Hinokitiol decreased pan-histone expression and impaired chromatin folding. Hinokitiol downregulated pan-histone expression by inhibiting the transcription. Hinokitiol suppressed the malignant phenotypes in vitro and tumourigenicity in vivo . Graphical Abstract: Abstract: Hinokitiol is reported to inhibit oral squamous cell carcinoma cells growth but its mechanism of action remains unclear. Hinokitiol induced cell cycle arrest in G1 or G1/S phase and induced cell apoptosis in oral squamous cell carcinoma cells. The cDNA microarray data showed 6.25–12.5 µM hinokitiol suppressed pan-histone mRNA expression and quantitative RT-PCR and western blotting showed the reproducibility of the results. Hinokitiol impaired the chromatin folding in oral squamous cell carcinoma cells. In addition, the binding of FLICE-associated huge protein and nuclear protein of the ataxia telangiectasia mutated locus on histone H4/e promoter was decreased, and H4/e promoter activity was significantly decreased. The malignant phenotypes of oral squamous cell carcinoma cells were suppressed in low dose (0.75–6.25 µM hinokitiol) in vitro . Feeding 10 mg/kg hinokitiol to mice suppressed xenograft tumourigenicity of HSC-3 cells in vivo . Hinokitiol showed the efficacy against oral squamous cell carcinoma cells growth by pan-histone suppression.